Midwives' tales : stories of traditional and professional birthing in Samoa - Barclay, Lesley (Vanderbilt University Press, 2005)
"This book allows Samoan midwives to speak for themselves about the variety of birthing practices in their country. Their accounts carry many important lessons for anyone concerned with human resource development in countries that are working to build sustainable health systems."--Jacket